2021
DOI: 10.1111/myc.13283
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of occurrence, seasonal variation and antifungal susceptibility of opportunistic Mucorales isolated from hospital soils in Iran

Abstract: Background Mucorales are opportunistic pathogens that can cause life‐threatening diseases predominantly in immunocompromised patients. Objectives This study aimed to investigate the frequency, seasonal variation and antifungal susceptibility of pathogenic Mucorales in the soil collected from seven hospitals in Urmia, Iran, between November 2017 and July 2018 in four different seasons. Methods Mucorales isolates obtained from soil were characterised based on conventional and molecular assays. In addition, in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…A study done in Iran in 2017–2018 isolated the maximum number of R. arrhizus from 196 soil samples and also found seasonal variation in isolation of Mucorales. In their study a seasonal variation in the frequency of Mucorales in soil was detected, with a maximum of culture-positive soil samples detected in wet autumn (43.2%), followed by winter (23.4%), summer (19.7%) and spring (13.6%) 12…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A study done in Iran in 2017–2018 isolated the maximum number of R. arrhizus from 196 soil samples and also found seasonal variation in isolation of Mucorales. In their study a seasonal variation in the frequency of Mucorales in soil was detected, with a maximum of culture-positive soil samples detected in wet autumn (43.2%), followed by winter (23.4%), summer (19.7%) and spring (13.6%) 12…”
Section: Discussionmentioning
confidence: 93%
“…In their study a seasonal variation in the frequency of Mucorales in soil was detected, with a maximum of culturepositive soil samples detected in wet autumn (43.2%), followed by winter (23.4%), summer (19.7%) and spring (13.6%). 12 Majority of these species have low MIC to AMB and PSC. Espinel-Ingroff et al 10 have also demonstrated similar findings in a multicentric study done in 13 centers worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Mucorales species are diverse across different countries. For example, Lichtheimia species are widespread in Europe and completely absent from the Americas [ 8 ]. Mucormycosis is also called zygomycosis or phycomycosis, and it is known misleadingly as ‘black fungus’, perhaps because of it may induce tissue necrosis, which eventually tends to be black in color [ 9 ].…”
Section: Mucormycosismentioning
confidence: 99%
“…Early detection of mucormycosis is important, as it can improve the prognosis. 30 31 32 According to studies, it improves survival, can minimize the need for or degree of surgical resection, and decrease disfigurement and suffering. 33 Since the illness is so uncommon, having a high index of suspicion is crucial.…”
Section: Prognosis and Diagnosismentioning
confidence: 99%